Peningkatan Kualitas Siswa dalam Pembelajaran Proyek Penguatan Profil Pelajar Pancasila (P5) Melalui Usaha Budidaya Jamur Tiram Putih (Pleurotus ostreatus) - Sufaati, Supeni; Suharno, Suharno; Tanjung , Rosye H.R.; Sopian, Yayan; Mushid, Totok A.; Juwita, Juwita; Parjan , Parjan; Busup, Eni Miton; Fakdawer, Nelince (Bakti Hayati: Jurnal Pengabdian Indonesia, 2023)
One of the implementations of the Merdeka Curriculum is the Pancasila Student Profile Strengthening Project (P5). The implementation of P5 at PGRI High School in Jayapura City for grade X students in the 2022-2023 school year carries the theme of Entrepreneurship with a focus on oyster mushroom cultivation. The purpose of this activity is to provide understanding, practice, and business of white oyster mushroom cultivation at PGRI High School in Jayapura City. The methods used include Focus Group Discussion, Participatory Planning and small-scale cultivation practices at the school level. The results of the activity showed that the students were very enthusiastic in participating in the activity, especially during the practice of white oyster mushroom cultivation. After this activity there was an increase in student knowledge about white oyster mushroom by 57.5% and its nutritional content (61%). In addition, the participants also became aware of the economic value of white oyster mushroom. Furthermore, 79.17% of students have understood how to cultivate white oyster mushroom. In general, 87.5% of students were happy to participate in this activity. Moreover, the students have succeeded in cultivating white  oyster mushroom independently with simple technology at school. The white oyster mushroom cultivation activity is very interesting for students to learn entrepreneurship, in accordance with the P5 theme at the school.